Pengaruh sales promotion cashback dan price discount terhadap perilaku impulse buying pengguna di situs belanja online tokopedia - Sya’diyah, Halimatus; Dwiridotjahjono, Jojok (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of Cashback and Price Discount on the Impulse Buying behavior of Tokopedia users, either directly or indirectly, and to find out how far the effect is. The population used in this study were UPN Veterans East Java students who used and had made transaction or purchases on the Tokopedia online shopping site with a total sample of 100 respondents. Sampling was done using probability sampling technique with simple random sampling method. The technique used in this research is using multiple linear regression analysisand using classical assumption test (normality test, multicolinearity test, heteroscedasticity test, autocorrelation test). The result of the study show that Cashback and Price Discount simultaneously have a significant effect on the Impulse Buying behavior of Tokopedia users. Cashback partially has a significant effect on the Impulse Buying behavior of Tokopedia users. Price Discount has a significant effecet on the Impulse Buying behavior of Tokopedia users..